ما اتفق عليه الحرميان وما انفردا فيه عن بقية القراء من خلال الشاطبية - سليمان، عبدالله إسحاق عبدالله (عبدالفتاح ادريس, 2018)
Praise be to Allah and prayers and peace be upon the Messenger of Allah and his family and companions. The researcher has used inductive and descriptive methods, by tracking what the Haramians agreed with others and what is unique in it from the rest of the readers through the Shattabiyah, in the approved references and studied a scientific study according to what is followed in scientific research. The researcher has divided this study into four topics. The researcher has dealt in the first topic: the translation of Imam Shati and the definition of Alshatabip and symbols. In the second topic: translation of the sanctuaries and in the third topic: what the Haramians agreed with others and what is unique in it from the rest of the readers in the assets. And in the fourth section: what the Haramians agreed with others and what is unique in it from the rest of the readers in the connotation. In conclusion: Hereby the researcher has addressed the most important findings, sources and references. The researcher has come out with the following findings: In the Denotation - The Haramain agreed: Nafie and Ibn Katheer with other readers in the section (letters near their exits) by showing the dal when the humiliation in: (Khais) the first Mary, and the dowry at the end in: (there is reward) in the two places, and W at the T: I heard), and what individuals and groups in the Holy Qur'an did to him: "How much did you utter?" - They are characterized in the chapter on their doctrines in the "Addings of the Addendum" in four words in the verse: "To make me sad to go with him" ("I am prepared to go out"), "You blindfold me" ("Order me to worship") In the Connotation -They agreed with each other in the following words: (a commandment for their spouses), (that we have for reward), (but we carried), (security is safe), (and Astberk and resolved). – They are characterized in the verse: (and if you do good, multiply it), (Vbm Tbshoron), (and filled with fear), (until the Tzaki), (you have addressed).
الحمد لله والصلاة والسلام على رسول الله وعلى آله وصحبه وسلم، اتبع الباحث في دراسة هذا الموضوع المنهج الاستقرائي والوصفي، وذلك بتتبع ما اتفق عليه الحرميان مع غيرهما وما انفردا فيه عن بقية القراء من خلال الشاطبية، في المراجع المعتمدة، ودراستها دراسة علمية وفق ما هو متبع في البحوث العلمية. وقسم الباحث هذه الدراسة إلى أربعة مباحث، تناول في المبحث الأول: ترجمة الإمام الشاطبي والتعريف بالشاطبية ورموزها. وفي المبحث الثاني: ترجمة الحرميان. وفي المبحث الثالث: ما اتفق عليه الحرميان مع غيرهما وما انفردا فيه عن بقية القراء في الأصول. وفي المبحث الرابع: ما اتفق عليه الحرميان مع غيرهما وما انفردا فيه عن بقية القراء في الفرش. وفي الخاتمة: تناول أهم النتائج والمصادر والمراجع. وفيما يلي: أهم النتائج التي تضمنته الدراسة: في الأصول: 1. اتفق الحرميان وهما: نافع وابن كثير مع غيرهما من القراء في باب (حروف قربت مخارجها) بإظهار الدال عند الذال في: (كهيعص) أول مريم، والدال عند الثاء في: (يُرِدْ ثَوَابَ) في الموضعين، والثاء عند التاء في: (لَبِثْتَ) وما تصرف منه إفرادا وجمعا في القرآن الكريم نحو: (كَمْ لَبِثْتُمْ). 2. انفردا في باب مذاهبهم في (ياءات الإضافة) في أربع كلمات في قوله تعالى: (لَيَحْزُنُنِي أَنْ تَذْهَبُوا بِه)، (أَتَعِدانِنِي أَنْ أُخْرَجَ)، (حَشَرْتَنِي أَعْمى)، (تَأْمُرُونِّي أَعْبُدُ). في الفرش: اتفقا مع غيرهما في كلمات الآتية وهي: (وصِيَّةً لأَزْوَاجِهِم)، (إنَّ لَنَا لأَجْرًا)، (ولَكِنَّا حُمِّلْنَا)، (أَمَّنْ هُوَ قَانِتٌ)، (وإسْتَبْرَقٌ وحُلُّوا). وانفردا في قوله تعالى: (وإن تَكُ حَسَنَةً يُضَاعِفْهَا)، (فَبِمَ تُبَشِّرُونَ)، (ولَمُلِئْتَ مِنْهُمْ رُعْبًا)، (إلَى أَن تَزَكَّى)، (فَأَنتَ لَهُ تَصَدَّى).
Keywords: الشاطبي، القاسم بن فيرة بن خلف، ت. 590 هـ -- ابن كثير المكي، عبدالله بن كثير، ت. 120 هـ -- نافع المدني، نافع بن عبدالرحمن بن أبي نعيم، ت. 169 هـ -- تفسير القرآن